The defined dish ebook Whole30 endorsed, healthy and wholesome weeknight recipes. - Snodgrass, Alex (A Defined Dish Book., 2019)
NEW YORK TIMES BESTSELLER! Healthy, easy, and delicious recipes from the Defined Dish blog—fully endorsed by Whole30 Alex Snodgrass of TheDefinedDish.com is the third author in the popular Whole30 Endorsed series. With gluten-free, dairy-free, and grain-free recipes that sound and look way too delicious to be healthy, this is a cookbook people can turn to after completing a Whole30, when they're looking to reintroduce healthful ingredients like tortillas, yogurt, beans, and legumes. Recipes like Chipotle Chicken Tostadas with Pineapple Salsa or Black Pepper Chicken are easy enough to prepare even after a busy day at work. There are no esoteric ingredients in these recipes, but instead something to suit every taste, each dish clearly marked if it is Whole30 compliant, paleo, gluten-free, dairy-free, and more. Alex includes delicious variations, too, such as using lettuce wraps instead of taco shells, to ensure recipes can work for almost any diet. And for anyone looking to stick to their Whole30 for longer, at least sixty of the recipes are fully compliant.